THE IMPACT OF HUMAN INTELLIGENCE ON THE ENGLISH-SPEAKING PROFICIENCY OF INDONESIAN ADULTS - Yenny Martasari; Agustinus Ngadiman (Widya Mandala Surabaya Catholic University, 2021)
This article reveals the impact of human intelligence on the English-speaking proficiency of Indonesian adults. The subjects of this study were Indonesian adults aged 18-40 years old as many as 41 subjects. The data of this study were Intelligence Quotient scores obtained through a logic test, Emotional Quotient and Spiritual Quotient scores obtained through a questionnaire, while English proficiency scores obtained through Focus Group Discussion. The results of this research led to the finding that Spiritual Quotient impacts English-speaking proficiency in comparison to Intelligence Quotient and Emotional Quotient.